Gefitinib-mediated apoptosis is enhanced via inhibition of autophagy by chloroquine diphosphate in cutaneous squamous cell carcinoma cells - Wang, Jianyu (Oncol Lett, 2019)
The development of cutaneous squamous cell carcinoma (cSCC) is associated with activation of the epidermal growth factor receptor (EGFR). EGFR-targeting presents a promising strategy for improving therapeutic efficacy. However, recent studies have suggested that tumours overexpressing EGFR depend on autophagy for survival and exhibit resistance to EGFR-targeting drugs. Chloroquine diphosphate (CQ), an autophagy inhibitor that may enhance the cytocidal effect of gefitinib against cSCC, was used in the present study. Cytotoxicity assays were performed to determine the half-maximal inhibitory concentration values of gefitinib and CQ in A431 cells. Drug interaction was analysed using CompuSyn software, which also determined combination index and dose reduction index values. Apoptosis and autophagy of A431 cells were investigated via flow cytometry, western blotting analyses, acridine orange/ethidium bromide staining and monodansylcadaverine staining. Suppression of autophagy by CQ, which was demonstrated by an alteration in microtubule associated protein 1 light chain 3-B in CQ pre-treated A431 cells, significantly enhanced cell apoptosis, which suggested that gefitinib-induced autophagy is cytoprotective. Thus, CQ was demonstrated to exhibit a synergistic apoptotic effect when used in combination with gefitinib during cSCC therapy. Further in vivo investigations are required to confirm the results of the present study.